Depression led pitting edema: A rarest case presentation - Khatri Sapkota, Niraj (International Journal of Health Sciences, 2017)
Pitting edema is the clinical manifestation generally presented due to long standing, especially during summer in the sun, heavy weight bearing, vasodilatation, or cardio-hepatorenal disease or in rare hypothyroidism, but in atypical case may demonstrates depression with progressive stress, that also shows indication of mild pitting edema. We present a case of a non-alcoholic 42 years divorced male under anti-anxiety medication for 10 years who complained of weight gain almost 10 kg in 30 days duration, less attentive to his work, and always feel sleepiness during day (once get to sleep, slept more than 5 h during day) and also late up to morning if not called to wake-up, also with diminished memory, more specific event was before 60 days of these symptoms he unexpectedly suffered family tragedy suggesting depression led progressive stress pitting edema that got managed after appropriate counseling along with changes in his life style.